Gestión antisoborno: evaluación en una economía Latinoamericana con base en la norma técnica NTCISO 37001:2017 - Monroy Estupiñan, Sergio Alberto (2022)
Bribery in the public sector erodes public trust in institutions and hinders the country's progress; Colombian legislation has established a set of provisions to prevent bribery, which can be complemented with proactive measures such as the application of international standards for anti-bribery management. This study analyzes the incorporation of anti-bribery management based on chapter 8 of the international technical standard NTC-ISO 37001: 2017 in the Colombian National Navy Acquisitions process. An instrument was designed and validated to diagnose anti-bribery management in officials and internal users of the process, and it was found as a relevant aspect that there is compliance in general with the risk management of bribery in the Acquisitions process; however, 25 gaps were identified with respect to the requirements proposed by NTC-ISO 37001: 2017. Based on the guidelines in Annex A of the aforementioned standard, a valid and viable proposal was developed to be applied in the entity, to close the identified gaps, divided into the communication and dissemination aspects of specific aspects to the group of collaborators of the Acquisitions process and adjustment to some institutional documents